2021
DOI: 10.12669/pjms.37.3.3552
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of subtypes and immunophenotypic characterization of 1379 cases of paediatric acute leukaemia

Abstract: Objectives: Acute leukaemia is the most common and highly curable childhood malignancy; subtyping and identification of antigens via immunophenotyping helps in treatment plan as well as minimal residual disease monitoring. Methods: This retrospective study was conducted at the Haematology section of the clinical laboratories of Ziauddin University Hospital and The Indus Hospital, Karachi conducted at January 1st, 2012 to December 31st, 2017. The study included 1379 cases of de novo acute leukemia from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Negativity for CD20, as B-cell specific marker was observed in 61.8% of B-ALL cases reported by Tong et al 26 Absence of CD10 expression was in 5% to 18.8% in eastern and western studies 26,32 and in this study, we found it 24% which is higher. It is an established fact that CD3 is the best marker for T-ALL, we found it 100% cases of T-ALL similar like other studies 33,34 but CD5 (33%) and CD7(33%) expressions found lower in this study may be due to small sample size. In this study, in case of AML maximum positivity was MPO (93.24%) followed by CD33 (86.58%), CD13 (79.92%) and CD117 (73.26%) but study from Pakistan and India shows that maximum positivity is for CD33 & CD13.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Negativity for CD20, as B-cell specific marker was observed in 61.8% of B-ALL cases reported by Tong et al 26 Absence of CD10 expression was in 5% to 18.8% in eastern and western studies 26,32 and in this study, we found it 24% which is higher. It is an established fact that CD3 is the best marker for T-ALL, we found it 100% cases of T-ALL similar like other studies 33,34 but CD5 (33%) and CD7(33%) expressions found lower in this study may be due to small sample size. In this study, in case of AML maximum positivity was MPO (93.24%) followed by CD33 (86.58%), CD13 (79.92%) and CD117 (73.26%) but study from Pakistan and India shows that maximum positivity is for CD33 & CD13.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, in case of AML maximum positivity was MPO (93.24%) followed by CD33 (86.58%), CD13 (79.92%) and CD117 (73.26%) but study from Pakistan and India shows that maximum positivity is for CD33 & CD13. 34,35 Also there is 6.66% aberrant expression of B-cell marker CD19 and T-cell marker CD3 (6.66%), CD5 (6.66%) and CD7 (6.66%) found in our study. Tien HF et al reported that in B-cell marker (7.5% cases) and Tcell marker (16.8% cases) may be present in case of AML.…”
Section: Discussionsupporting
confidence: 50%
“…In two studies, the frequency of TDT-negative among a series of B-ALL ranged between 2.5 and 11%, where it was evaluated by both FC and immunohistochemistry (IHC). 2 4 5 Another larger study of 917 patients demonstrated a TDT-negative rate of 2.3%, which was examined by FC only. 6 The authors found that TDT-negative patients tended to be younger, had high WBC count, and carried KMT2A-r mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The most common childhood cancer is acute lymphoblastic leukemia (ALL), with 80-85% of cases coming from the B lineage. 1 , 2 Childhood B lymphoblastic leukemia (B-ALL) usually has a good prognosis, with a cure rate approaching 90% in high-income countries. 3 , 4 This improvement in outcome is a result of appropriate risk stratification, the introduction of risk-adjusted treatment protocols, and better supportive care.…”
Section: Introductionmentioning
confidence: 99%